2016
DOI: 10.1108/jaee-03-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

New public management and budgeting practices in Tanzanian Central Government

Abstract: Purpose The purpose of this paper is to investigate the budgeting practices in the Tanzanian Central Government. New budgeting reforms were introduced following exhortations from the bodies such as the UN, the World Bank and the IMF and reflect the new public management (NPM). Design/methodology/approach A grounded theory methodology was used. This methodology is inductive, allowing phenomena to emerge from the participants rather than from prior theory. This ensures both relevance and depth of understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 91 publications
2
42
0
2
Order By: Relevance
“…This can be interpreted as an important factor for failure in PBB implementation at PURI. Our results support the conclusions of Goddard and Mkasiwa (2016), who referred to a gap between established formal rules and actual practice in public budgeting in Tanzania. They concluded that this occurred when there is a power conflict or self-interested of parties to the negotiation.…”
Section: Discussionsupporting
confidence: 91%
“…This can be interpreted as an important factor for failure in PBB implementation at PURI. Our results support the conclusions of Goddard and Mkasiwa (2016), who referred to a gap between established formal rules and actual practice in public budgeting in Tanzania. They concluded that this occurred when there is a power conflict or self-interested of parties to the negotiation.…”
Section: Discussionsupporting
confidence: 91%
“…Lassou (2017) (Bakre et al, 2017;Van Wyk, 2007). As such, calls have been made to expand our understanding of local contexts and factors, which tend to influence the implementation of accrual accounting in emerging economies (Harun et al, 2012 andSoobaroyen et al, 2017 (Adhikari and Jayasinghe, 2017;Salah et al, 2018), Tanzania appears to be determined to conform to accrual accounting reforms, but is 'struggling for conformance' (Goddard and Mkasiwa, 2016;. We add to extant work in public sector accounting in…”
Section: Public Sector Accounting Reforms In Emerging Economies With mentioning
confidence: 97%
“…Accounting has become an important means for these organisations through which to promote their neo-liberal ideas and professional expertise, as well as to secure high-paid employments for their consultants in emerging economies (Hopper et al, 2017;Josiah et al, 2010;Alawattage et al, 2007;Hopper et al, 2009;Neu et al, 2009). Prior work shows that accounting techniques, such as participatory budgeting, accrual accounting and, more recently, the Cash Basis IPSAS, have been widely disseminated to emerging economies by these international organisations, predicating improvements in transparency and accountability in resource allocation and service delivery (Goddard and Mkasiwa, 2016;Kuruppu et al, 2016;Bakre et al, 2017;Uddin et al, 2011;Harun et al, 2012;Yapa and Ukwatte, 2015;Parry and Wynne, 2009;Adhikari and Mellemvik, 2010). Adhikari and Jayasinghe (2017) state that public sector accounting reforms, mainly the adoption of accrual accounting and IPSASs in emerging economies, have, however, experienced unintended consequences and failures.…”
Section: Introductionmentioning
confidence: 99%